Robust T-S Fuzzy Control of Electrostimulation for Paraplegic Patients considering Norm-Bounded Uncertainties - Covacic, Márcio Roberto; Minhoto Teixeira, Marcelo Carvalho [UNESP]; Augusto De Carvalho, Aparecido [UNESP]; Cardim, Rodrigo [UNESP]; Assunção, edvaldo [UNESP]; Sanches, Marcelo Augusto Assunção [UNESP]; Fujimoto, Henrique Shuiti; Mineo, Maxwell Simões; Biazeto, Anderson Ross [UNESP]; Gaino, Ruberlei (Hindawi, 2020)
This manuscript presents a Takagi-Sugeno fuzzy control for a mathematical model of the knee position of paraplegic patients using functional electrical stimulation (FES). Each local model of the fuzzy system is represented considering norm-bounded uncertainties. After obtaining the model of FES with norm-bounded uncertainties, the fuzzy control strategy is designed through the solution of linear matrix inequalities (LMIs) using the conditions available in the literature, which consider these norm-bounded uncertainties. The strategy considers decay rate and constraints on the input signal. The model is simulated in the Matlab environment using the numerical parameters measured by experimental tests from a paraplegic patient.